Humeral surface replacement for the sequelae of fractures of the proximal humerus - Pape, Guido; Zeifang, Felix; Bruckner, Thomas; Raiss, Patric; Rickert, Markus; Loew, Markus (Journal of bone and joint surgery. B, British volume, 2010)
Humeral surface replacement for the sequelae of fractures of the proximal humerus
Gesehen am 26.06.2023